PENERAPAN STATISTICS PROCESS CONTROL DALAM PENGAMATAN SIFAT FISIKA DAN KIMIA AIR BUANGAN DARI AIR CONDITIONING (AC) - Titik Indrawati; Nunung Isnaini Dwi Ningsih (Integrated Lab Journal, 2018)
Statistics Process Control (SPC) is a tool used for on-line quality control in mass production. Control Charts or control charts are selected from statistical sampling theory that is effectively applied in SPC. This paper will explain the function and method of applying one of the tools in SPC to observe the physical and chemical properties of wastewater from air conditioner (AC). The physical and chemical properties observed were TDS, pH, DHL, temperature, and turbidity. The results of the application of SPC by using the control chart shows that the control chart makes it easy for the observer to do the analysis process of the observation data. The results obtained can be taken from SPC on the observation of the physical and chemical properties of AC waste water in the Environmental Laboratory of the Faculty of Biology, Jenderal Soedirman University, namely the average value of each parameter, namely TDS = (4.85 mg / L), pH = 6.53, DHL = 0.00117 (ms), temperature = 23.3C, Turbidity = 0.4265 (NTU). Referring to the requirements of distilled water, the AC waste water is still suitable for use as a substitute for distilled water. The ploting of data on the Xbar-chart TDS data, pH, and Turbidity is within the control limit with a confidence level of 99%, while the Temperature and DHL data are within the control limit with a 95% confidence level. While the results of plotting the data on the Rbar-chart of TDS, DHL, and Temperature data are within the control limits with a 99% confidence level, while the pH and Turbidity data are within the control limits with a 95% confidence level.